Elevated homocysteine level as an indicator for chronic kidney disease in community-dwelling middle-aged and elderly populations in Taiwan: A community-based cross-sectional study - Shih, Yu-Lin; Shih, Chin-Chuan; Chen, Jau-Yuan (Frontiers in Medicine, 2022)
Abstract Background: Hyperhomocysteinemia is an important factor for endothelial cell damage and a risk factor for cardiovascular diseases. Chronic kidney disease (CKD) is recognized as a leading burden in Taiwan’s healthcare system. This study aimed to investigate the association between homocysteine levels and CKD in middle-aged and elderly adults from a community in northern Taiwan. Methods: A total of 396 middle-aged and elderly Taiwanese adults were enrolled and completed the health survey. We divided participants according to tertiles of homocysteine levels as low, middle, and high levels. CKD was defined as estimated glomerular filtration rate (eGFR) <60 (mL/min/1.73 m2) or urine albumin to creatinine ratio >30 (mg/g). Pearson correlation was calculated between eGFR and other related risk factors after adjustment for age. The risk of CKD in the middle and high homocysteine groups compared to that in the low homocysteine group was assessed by multivariate logistic regression after adjustment for age, sex, smoking, hypertension (HTN), diabetes mellitus (DM), body mass index (BMI), dyslipidemia, and uric acid. The Youden index and receiver operating characteristic (ROC) curve were calculated for the optimized cutoff value. Results: Elevated plasma homocysteine levels were more likely to lower the eGFR and increase the prevalence of CKD. Pearson correlation showed a positive correlation between eGFR and high-density lipoprotein cholesterol, while a negative correlation was observed between homocysteine levels, waist circumference, systolic blood pressure, and BMI (all p<0.05). In the logistic regression analysis, the prevalence of CKD increased, as well as the homocysteine level. The odds ratio of CKD under 95% confidence interval was 2.655 (1.284–5.490) for the high homocysteine level group compared with the low homocysteine group after adjusting for age, sex, smoking, DM, HTN, dyslipidemia, uric acid, and BMI (p=0.008). The area under the ROC curve was 0.662, and a cutoff value of 15.15 µmol/L for the homocysteine level was obtained. Conclusion: Our study findings revealed that elevated homocysteine levels were significantly associated with CKD and could be used as an indicator of CKD among the middle-aged and elderly populations in Taiwan.